Developing characterization factors to quantify management impacts on soil quality of paddy fields within life cycle assessment. (20th November 2019) - Tang, Longlong; Hayashi, Kiyotada; Ohigashi, Kentaro; Shimura, Motoko; Kohyama, Kazunori
Abstract: Soil quality varies greatly with the management of agricultural land such as the application of fertilizer. Quantifying the impact on soil quality at a management level has been recognized as an urgent issue in life cycle assessment (LCA). This study is the first to estimate characterization factors for land occupation under different soil type, fertilizer type, and application period, which is defined as 1 (the optimum quality of a soil) minus the soil quality index (SQI). The SQI for paddy field of Japan are estimated as follows. First, SQI at each site per year was calculated by considering five soil functions and 17 soil properties collected from a long-term soil monitoring database. Then, time-dependent SQIs over 20 years were then estimated using a statistical model for different combinations of three soil types and five fertilizer types (chemical fertilizers, chemical fertilizers with rice straw, chemical fertilizers with rice straw compost, rice straw, and rice straw compost). The results showed that the SQI is influenced by both soil type and fertilizer type. For fertilizer type, continuous use of chemical fertilizers lowered the SQI. The addition of rice straw to chemical fertilizers mitigated the decrease of the SQI, but the addition of more compost increased the SQI. Longer application periods led to larger differences between the SQI of each fertilizer type, which suggests that it is important to calculate time-dependent characterization factors. The introduction of soil quality impact assessment based on the new characterization factors into an LCA of agricultural system is expected to improve to capture the difference among managements of agricultural land. Graphical abstract: Image 1 Highlights: The soil quality index (SQI) is used to estimate characterization factors of soil quality for paddy fields. The SQI in 20 years for combinations of 3 soil types and 5 fertilizer types are predicted. Long-term continuous use of chemical fertilizers lowered the SQI. The addition of compost to chemical fertilizers mitigated the decrease in the SQI. The longer the application period, the larger the differences between the SQI of fertilizer types.